The effectiveness of games learning method in national defense preparedness subject on basic training for civil servant candidates - Des Indri Prihantony (Monas: Jurnal Inovasi Aparatur, 2020)
The selection of suitable learning methods will determine the success of a learning process. In the state defense preparedness training program, games are one of the methods used to achieve learning objectives through the use of playful media. This study aims to assess the effectiveness of this learning method and the factors supporting the effectiveness. The study was conducted on participants in Basic Training for Civil Servants Candidates in 2019 in West Sumatra Province through the distribution of questionnaires online. The results showed that 98.8 % of respondents considered that this method was effective.